Interaction Study, Synthesis and Characterization of Molecular Imprinted Polymer Using Functional Monomer Methacrylate Acid and Dimethylamylamine as Template Molecule - Saeful Amin; Sophi Damayanti; Slamet Ibrahim (JURNAL ILMU KEFARMASIAN INDONESIA, 2018)
The research related to the interaction study, synthesis and characterization of molecular imprinted polymer using dimethylamylamine (DMAA) as the template molecule and the functional monomer methacrylate acid has been conducted. Molecular Imprinted Polymer (MIP) is a separation method made by the molecule template in the polymer matrix followed by removing the template molecule by washing for giving the permanent framework groove. The MIP was made by mixing the DMAA as the template molecule, with the methacrylate acid as the functional monomer, and the ethylene glycol dimethacrylate (EGDMA) as the crosslinker with the ratio 1:6:20. Porogen solvents used were the chloroform and the initiator azobisisobutyronitrile (AIBN). The crystal MIP and the NIP without the DMAA were characterized using Infrared Spectrophotometer (FTIR), and the result showed that there have been differences among the MIP, the NIP and the MIP after being extracted. The characterization using Scanning Electron Microscope (SEM) showed that the NIP as the comparison having flat morphology, while the MIP having irregular morphology and less pores. Then the MIP after being extracted has irregular, rough morphology and a lot of pores. The result reveals the interaction between the DMAA and the methacrylate acid that is the hydrogen bonded with the Gibbs free energy obtained is -5.434 j/mol. The imprinting factor of 2,353 is obtained. The highest desorption descending capacity is chloroform with the MIP 738% better. For the MIP and NIP methanol, it is found that the MIP is 123% better. Then the MIP which is desorbed by the chloroform is better 602% than the MIP resorbed by the methanol, and the ethyl acetate cannot desorb the DMAA.